스마트 팩토리를 위한 빅 데이터 기반 분석 플랫폼 - 사공운(Woon Sagong); 장용훈(Yonghun Jang); 손영욱(Yeongwook Son); 박창현(Changhyeon Park) (정보과학회 컴퓨팅의 실제 논문지, 2018)
ICT와 생산 제조기술이 융합된 스마트 팩토리가 산업현장에 점차 적용됨에 따라, 생산 제조관련 데이터는 기하급수적으로 생산되고 있다. 이렇게 생성되는 원시 데이터는 제조 공정에 대한 숨은 정보들을 포함하고 있지만, 양이 방대하여 이를 처리하기 위한 적절한 플랫폼이 필요하다. 본 논문에서는 생산 제조업에서 축적된 빅데이터를 보다 쉽고 편리하게 가공하고 분석하기 위한 분석 플랫폼을 제안하고 이를 이용한 분석결과를 소개한다. 제안하는 분석플랫폼은 효율적인 빅데이터 수집을 위해 스쿱과 우지를 이용하였고 신속한 사용자 질의처리를 위해 하둡, 하이브, 스파크를 활용한다. 또한 데이터 분석과 시각화를 위해 고급 분석 도구인 R을 하이브에 연동하여 사용한다. 분석 플랫폼을 이용하여 국내 생산 제조업체의 사출 공정 데이터를 수집하고 통계적 분석을 이용한 불량률과 관련된 분석을 진행한 결과, 사출작업 간 원재료의 각 속성 값과 습도가 감소하거나 기온이 상온에서 멀어질수록 불량률이 증가함을 확인하였다. As the Smart Factory which combines ICT and manufacturing technologies is gradually being applied to industrial sites, manufacturing data is being produced exponentially. The raw data contains hidden information about the manufacturing process; however, a customized platform is needed for massive data processing. In this paper, we propose the analytics platform for analysis and processing with easy and convenient storage of big data about the manufacturing and also introduce results of the analysis. The proposed analytics platform uses sqoop and oozie to collect big data effectively and uses hadoop, hive, and oozie to process user queries in a fast pace. It also applies R which is a high-level analysis tool for data analysis and visualization. We collected data generated in the injection molding processing of any specific manufacture company using the proposed analytics platform, and analyzed it with statistical analysis for the rate of defectives. It was observed that the rate of defectives increased with a decrease in the properties of the raw material and humidity or the difference in room temperature. KCI Citation Count: 2